Analisis Bibliometrik Sertifikasi Halal UMKM: Tren, Kontribusi, dan Arah Riset Masa Depan - Hesti Ismawarsih; Luqman Hakim Handoko; Azis Budi Setiawan (ISLAMIC BUSINESS and FINANCE, 2025)
This study aims to map the development of literature related to halal certification in Micro, Small, and Medium Enterprises (MSMEs) through a bibliometric approach based on Google Scholar data. The method used is a combination of quantitative and qualitative approaches (mixed method), with bibliometric techniques for statistical analysis and systematic literature review for thematic interpretation. Secondary data was obtained through the Publish or Perish application, and analyzed using VOSviewer. The results show that from 2017 to November 2024, there were 133 relevant documents. The most productive author is Fajar from Trunojoyo University (4 publications) and the most productive institution is Trunojoyo. The author with the highest citation rate is Alissa Qotrun Nadya (55 citations). Dominant keywords include "halal certification", while terms such as "branding" are starting to appear in the latest trends, and "halalpreneurship" is relatively rarely used. This study also identified seven clusters of potential research topics based on network and overlay visualization. In addition, there are 6 research topics based on the literature review. These topics can be the basis or guide for the direction of the strategy for developing halal certification research for MSMEs in the future. Keywords: Halal Certification; MSMEs; Bibliometrics